Advanced nanomaterials and their applications in renewable energy - Liu, Jingbo Louise; Sajid, Bashir (Elsevier, 2015)
Advanced Nanomaterials and Their Applications in Renewable Energy presents timely topics related to nanomaterials' feasible synthesis and characterization, and their application in the energy fields. In addition, the book provides insights and scientific discoveries in toxicity study, with information that is easily understood by a wide audience. Advanced energy materials are important in designing materials that have greater physical, electronic, and optical properties. This book emphasizes the fundamental physics and chemistry underlying the techniques used to develop solar and fuel cells with high charge densities and energy conversion efficiencies. New analytical techniques (synchronous X-ray) which probe the interactions of particles and radiation with matter are also explored, making this book an invaluable reference for practitioners and those interested in the science.